TINJAUAN YURIDIS TERHADAP UNDANG-UNDANG TENTANG PERADILAN TATA USAHA NEGARA - Aju Putrijanti (Masalah-Masalah Hukum, 2011)
As a Constitutional State, there should be Administrative Tribunal with tasks to protect human nghts of citizenship in administration law. In Indonesia the Administrative Tribunal were found by Act Number 5 year 1986, and it has been change two times with dffferent background and different changes for each. In Act Number 5 year 1986 was found the basic principle to proceed in Administrative Tribunal. Act Number 9 year 2004, there are some changes in the act, especially for the execution of Administrative Tribunal Decree. Act Number 51 year 2009 was the second change from the first. The latest change mainly to raising the supervision for judge, the formation of special court under the Administrative Tribunal. the execution of Administrative Tribunal Decree, and also to reach the main goal. the integrated justice system.